2020
DOI: 10.1186/s12960-020-00515-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of shift work in the self-reported health and wellbeing of long-term and assisted-living professional caregivers in Alberta, Canada

Abstract: Background Numerous studies have found negative outcomes between shift work and physical, emotional, and mental health. Many professional caregivers are required to work shifts outside of the typical 9 am to 5 pm workday. Here, we explore whether shift work affects the health and wellbeing of long-term care (LTC) and assisted-living (AL) professional caregivers. Method The Caring for Professional Caregivers research study was conducted across 39 LTC and AL facilities in Alberta, Canada. Of the 1385 questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Among the work characteristics, longer working hours (more than 46 h/week) for women and night shift jobs for both men and women aged 30 years or above were found to be the most common predictors of high burnout. These findings support the results of a previous study conducted in Taiwan and other countries 13 , 33 35 .…”
Section: Discussionsupporting
confidence: 92%
“…Among the work characteristics, longer working hours (more than 46 h/week) for women and night shift jobs for both men and women aged 30 years or above were found to be the most common predictors of high burnout. These findings support the results of a previous study conducted in Taiwan and other countries 13 , 33 35 .…”
Section: Discussionsupporting
confidence: 92%
“…However, a positive organizational context may mitigate some of the negative consequences of working the night shift (or evening shifts) to a certain extent [ 32 , 33 ]. There is evidence to suggest that employees working night shifts experience more positive outcomes when they are allowed input, choice and flexibility in their work schedules [ 34 37 ]. In addition, Zhang et al [ 33 ] found that sleep quality and duration improved among shift workers (and especially for night-shift workers) in accordance with each beneficial work environment feature introduced.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of exercise among workers with NSWSs may also contribute to obesity risk. Night work has been shown to be associated with less exercise in assisted living caregivers [ 25 ], although not in nurses [ 26 ]. The link between NSWSs and exercise is not fully explored.…”
Section: Discussionmentioning
confidence: 99%